2017
DOI: 10.1158/1078-0432.ccr-16-2987
|View full text |Cite
|
Sign up to set email alerts
|

Global Protease Activity Profiling Provides Differential Diagnosis of Pancreatic Cysts

Abstract: Purpose Pancreatic cysts are estimated to be present 2–3% of the adult population. Unfortunately, current diagnostics do not accurately distinguish benign cysts from those that can progress into invasive cancer. Missregulated pericellular proteolysis is a hallmark of malignancy, and therefore, we used a global approach to discover protease activities that differentiate benign nonmucinous cysts from premalignant mucinous cysts. Experimental Design We employed an unbiased and global protease profiling approach… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…98 Promising biomarker results with PCF have also been reported for differentially methylated DNA, telomerase activity, protease expression, and the overexpression of Das-1. [99][100][101][102] However, the majority of these biomarkers have not been rigorous validated in a diverse cohort of pancreatic cysts. Hence, this is the goal of the Pancreatic Cyst Biomarker Validation Study, an ongoing double-blinded PCF biomarker study that is sponsored by the National Cancer Institute Early Detection Research Network.…”
Section: Pcf Diagnostics For Early Detection Of Progressionmentioning
confidence: 99%
“…98 Promising biomarker results with PCF have also been reported for differentially methylated DNA, telomerase activity, protease expression, and the overexpression of Das-1. [99][100][101][102] However, the majority of these biomarkers have not been rigorous validated in a diverse cohort of pancreatic cysts. Hence, this is the goal of the Pancreatic Cyst Biomarker Validation Study, an ongoing double-blinded PCF biomarker study that is sponsored by the National Cancer Institute Early Detection Research Network.…”
Section: Pcf Diagnostics For Early Detection Of Progressionmentioning
confidence: 99%
“…biospecimens (21)(22)(23)(24). Recent approaches leveraging synthetic substrates have used dropletbased microfluidics (25) or highly multiplexed peptide libraries (26,27) to profile protease activity in patient-derived biospecimens. However, these assays do not provide insight on spatial localization of protease activity within the tissue.…”
Section: Several Methods Have Been Developed With the Aim Of Measurinmentioning
confidence: 99%
“…The MSP‐MS assay has been used with protease inhibitors, gene deletions, and immunodepletion in combination with traditional proteomic methods to identify component proteases that are highly active in complex biological samples. This has enabled the “deconvolution” of proteolytic signatures from fungal pathogens, parasitic organisms, cancer cell lines, and patient samples, and allowed for the prioritization of proteases based on their functional contribution to the global substrate specificity profile. For example, the MSP‐MS assay was used to analyze the global activity signatures of the opportunistic fungal pathogen Candida albicans in the planktonic and biofilm states .…”
Section: Multiplex Substrate Profiling By Mass Spectrometrymentioning
confidence: 99%
“…Comparison of the activity signatures from each state coupled to inhibitor and proteomic analysis revealed that two specific secreted aspartyl proteases (Saps) are upregulated during biofilm growth and are critical to biofilm formation in vitro and in vivo. MSP‐MS was also recently used to identify two human aspartyl proteases that are selectively upregulated in cystic precursor lesions of pancreatic cancer . This strategy enabled the development of a highly accurate diagnostic assay using fluorogenic substrates for differentiating benign and premalignant lesions within a cohort of patient cyst fluid samples.…”
Section: Multiplex Substrate Profiling By Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation